2019
DOI: 10.1002/ptr.6364
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferitrin inhibits proliferation, induces apoptosis, and ameliorates inflammation in human rheumatoid arthritis fibroblast‐like synoviocytes

Abstract: Rheumatoid arthritis (RA) is a complex chronic inflammatory disease that is associated with the aberrant activation of fibroblast‐like synoviocytes (FLS). Kaempferitrin is a natural flavonoid glycoside that possesses anti‐inflammatory bioactivity. However, the effect of kaempferitrin on RA has not yet been revealed. The aim of the present study was to investigate the effect of kaempferitrin on human RA‐FLS MH7A cell line. We found that kaempferitrin inhibited proliferation and induced apoptosis of MH7A cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 29 publications
2
39
1
Order By: Relevance
“…Mitochondrial mediated apoptosis is largely regulated by the Bcl-2 protein family. It is well known that the Bcl-2 family proteins, anti-apoptotic proteins such as Bcl-2, inhibit apoptosis, while pro-apoptotic proteins, such as Bax, activate apoptosis in RA [29]. In this study, our results showed that Cinnamomi ramulus increased the expression of Bax in MH7A, as well as decreased the expression of Bcl-2 protein.…”
Section: Cinnamomi Ramulus Extracts Inhibits Cell Migration and Invassupporting
confidence: 58%
“…Mitochondrial mediated apoptosis is largely regulated by the Bcl-2 protein family. It is well known that the Bcl-2 family proteins, anti-apoptotic proteins such as Bcl-2, inhibit apoptosis, while pro-apoptotic proteins, such as Bax, activate apoptosis in RA [29]. In this study, our results showed that Cinnamomi ramulus increased the expression of Bax in MH7A, as well as decreased the expression of Bcl-2 protein.…”
Section: Cinnamomi Ramulus Extracts Inhibits Cell Migration and Invassupporting
confidence: 58%
“…The results of clinical manifestations and pathological changes demonstrated that WJT played an important role in suppressing the pathological progression of arthritis in CIA rats, which laid a foundation for the further study. In addition, The aberrant release and recruitment of pro-in ammatory cytokines (TNF-α, IL-1β, and IL-6) are essential to the pathogenesis of RA [17,29,20]. It's well known that both TNFα and IL-1β play roles in the activation and in ltration of immune cells, and contribute to production of in ammatory cytokines and chemokines, thereby resulting in a complex network that promotes in ammatory reactions, cartilage damage and autoimmune pathology [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…The results of clinical manifestations and pathological changes demonstrated that WJT played an important role in suppressing the pathological progression of arthritis in CIA rats, which laid a foundation for the further study. In addition, The aberrant release and recruitment of pro-in ammatory cytokines (TNF-α, IL-1β, and IL-6) are essential to the pathogenesis of RA [18,20,21]. It's well known that both TNFα and IL-1β play roles in the activation and in ltration of immune cells, and contribute to production of in ammatory cytokines and chemokines, thereby resulting in a complex network that promotes in ammatory reactions, cartilage damage and autoimmune pathology [18,22].…”
Section: Discussionmentioning
confidence: 99%